Analysis of an Agmatine Deiminase Gene Cluster in Streptococcus mutans UA159 - Griswold, Ann R. (American Society for Microbiology, 2004)
An operon encoding enzymes of the agmatine deiminase system (AgDS) has been identified in the cariogenic bacterium Streptococcus mutans UA159. The AgDS is regulated by agmatine induction and carbohydrate catabolite repression. Ammonia is produced from agmatine at low pH, suggesting that the AgDS could augment acid tolerance.